AUTONOMOUS WATER LEVEL GAUGE: ASSEMBLY AND TESTING ON THE OREDEZH RIVER (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
This paper presents the testing of an autonomous system for measuring water levels in a body of water using a hydrostatic level gauge. A technical description of the system's components, assembly, and operation are provided. The system's startup and calibration processes, conducted on the Oredezh River in the Leningrad Region, are described. The article presents the initial results of the system's operation and identifies further steps for optimizing its performance.
Keywords: water level; hydrostatic sensor; autonomous system; Arduino